Analisis Rekonsiliasi Fiskal Terhadap Laporan Keuangan Komersial Pada PT. XXX Tahun 2019 - Andreas Hermawan Purnamawati Helen Widjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to find out whether the preparation of fiscal financial statements at PT. XXX is in accordance with the applicable Taxation Law, knowing the application of fiscal reconciliation to the commercial financial statements of PT. XXX, knowing the causes of the differences in financial statements on a commercial and fiscal basis as well as knowing the impact that occurs on the company's financial statements after a fiscal correction has been made which is the basis for calculating the Corporate Income Tax payable. Data collection methods in this study are the Library Research method and the Field Research method that is collected by commercial financial reports, fiscal financial reports and Annual SPT. Data analysis techniques using quantitative analysis. The results of this study indicate the existence of an expense and income account that has not been made a fiscal correction so that the income tax payable PT. XXX in 2019 did not comply with the applicable tax provisions.